PERBANDINGAN PENGGUNAAN MEDIA PEMBELAJARAN BENDA KONKRET DAN ELEKTRONIK DALAM MENGAKTIFKAN BELAJAR MATEMATIKA SISWA KELAS 1 SDN 131/IV KOTA - Maryono; Issaura , Sherly Pamela; Salvatira Nabila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to: (1) describe students’ activeness in learning mathematics when using concrete learning media, (2) describe students’ activeness in learning mathematics when using electronic (audiovisual) learning media, and (3) describe the comparison of students’ activeness in learning mathematics when using concrete and electronic (audiovisual) learning media. The research method used is descriptive quantitative. Data collection techniques include direct observation and documentation. Data were obtained through scaled instruments and descriptive observations based on predetermined aspects of learning activeness. The collected data were categorized based on the type of learning media used, namely during mathematics learning in first-grade elementary students using concrete media in the form of diagram pictures, and during the use of electronic (audiovisual) media in the form of instructional videos. This type of research does not use a hypothesis. The research results show that students’ activeness in learning mathematics was higher when using concrete learning media. Students were more focused during the learning process and showed great interest in participating in new activities and experiments related to the material. The classroom atmosphere became more active throughout the lesson. Students were also more capable of completing tasks and responding to the teacher’s explanations. Emotionally, students demonstrated increased respect for their peers, better interaction with both teachers and classmates, and greater confidence and ability to express their opinions during the learning process. The activeness of first-grade students at SDN 131/IV Kota Jambi increased more significantly during mathematics lessons using concrete learning media compared to electronic (audiovisual) media. This is because concrete media allow students to be directly involved in the learning process, thereby enhancing their interest and engagement, facilitating their understanding of the material, and improving their ability to analyze learning concepts. This effectiveness is attributed to the limited attention span of first-grade students, making learning media that involve physical activity and hands-on experiences more effective in improving focus and learning engagement. In contrast, when using electronic (audiovisual) learning media, most students paid less attention to the teacher during material explanations and demonstrations. Many appeared bored, as the instructional videos were only displayed on the board, and the image quality was suboptimal. Students seated farther from the screen had difficulty seeing the material clearly. However, they were still able to answer the teacher’s questions and complete tasks well, though they appeared less focused and enthusiastic during the mathematics lesson. Electronic media use is sometimes less effective for first-grade students, as it can lead to boredom or distraction if not used appropriately.